ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL KONTROL LIKUIDITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 – 2019 - Vincent Loekito; Loh Wenny Setiawati (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2021)
Firm value is an important factor for the company, because the firm value is not only a determinant of the condition of the company, but it can also attract investors to invest in the company. High stock prices make the market believe in the company's current performance and also the company's future prospects. This means that company managers must think about the company's image in the eyes of shareholders by implementing corporate social responsibility. Other factors which are the internal characteristics of the company that are able to influence firm value are liquidity, leverage, company size, and profitability. This study aims to analyze the effect of corporate social responsibility on firm value with the control variables of liquidity, leverage, company size, and profitability in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017–2019. This study used purposive sampling technique with 156 observation data using multiple linear regression. The results of this research indicate that corporate social responsibility has no effect on firm value, while the control variables firm size and profitability have an effect on firm value, and liquidity and leverage have no effect on firm value.